A prospective case series on surgical treatment of circumferential and semi-circumferential defects due to peri-implantitis - Luigi CANULLO; Luca SIGNORINI; Roberto PISTILLI; Romeo PATINI; Valeria PISTILLI; Paolo PESCE
Abstract Different surgical treatment strategies for peri-implantitis with the use of graft material and membranes have been suggested without any longitudinal remarkable success rate. The present preliminary study was aimed to analyze a new clinical approach based on the disinfection of the implant connection, the disinfection of the implant surface and GBR approach in the treatment of circumferential and semi-circumferential bony defect resulting from peri-implantitis. Six consecutive patients were selected for the present study. After removal of factors that could potentially influence peri-implant pathology, the prosthetic rehabilitation was always removed and a full thickness flap was elevated to allow access to the peri-implant defect and the exposed implant surface. Once the defect was degranulated and the implant surface cleaned, a mixture (50:50) of autogenous bone and allograft was used. Guided bone regeneration technique using membranes was adopted and the flaps were closed for a submerged healing. Six months thereafter, a new re-opening procedure was performed and cleaned superstructures and crowns were repositioned. Patients were followed for one year thereafter and recalled for a customized oral hygiene every three months. Radiological and periodontal analysis was performed before surgery and every six months. The studied procedure was associated with a pronounced increase in REC and CAL with stable peri-implant conditions at 6 and 12 months. PI, BOP and PD values were significantly reduced both at 6 and 12 months. At 12 months, a mean PD gain of 4.5 mm and a bone loss reduction of 5.1 mm was obtained. Within the limitation of the present preliminary study, the proposed technique might represent a promising result for treatment of circumferential and semi-circumferential bone defects around implants affected by peri-implantitis.